A guide to research methodology : an overview of research problems, tasks and methods - Mukherjee, Shyama Prasad (New York CRC press, 2020)
"The present book attempts to provide readers with a broad framework for research in any field. Attention has been given to provide illustrations from different disciplines. Problems of data collection using survey sampling and design of experiments as well as methods of data analysis and the associated use of models have been discussed"--
Keywords: Research -- Methodology